PENGARUH ZIS PRODUKTIF TERHADAP KINERJA DAN KESEJAHTERAAN UMK MUSTAHIK - Afriandi, Redho; Muttaqien, Muhammad Khaerul (Kopertais Wilayah I DKI Jakarta dan Banten, 2018)
In general, this study aims to determine the effect of programs Zakat, Infaq and Sadaqah (ZIS) Productive to the performance of micro-enterprises and prosperity mustahik; while specifically the purpose of this study is to test and analyze the effect of productive ZIS programs on the performance of mustahik micro enterprises and mustahik welfare. This study was conducted in Bogor and Depok districts of West Java. Data collection was done by survey method by taking samples of 89 mustahic households as respondents. Data analysis was done by quantitative approach and completed with qualitative and intuitive analysis. Quantitative approach used is Partial Least Square (PLS) model, while data processing is executed with SmartPLS program version 3.0. Based on the analysis result, it can be concluded that productive ZIS program can improve the performance of UMK mustahik. Improved performance represented by an increase in assets and profits can also make it easier for UMK mustahik to achieve better welfare.